A Retrospective Review on Post Traumatic Agitation Predictors in Hospitalized Patients with Acute Traumatic Brain Injury - Jehane H. Dagher; Jennifer Massad; Julie Lamoureux; Elaine de Guise; Mitra Feyz (Journal of Basic & Applied Sciences, 2019)
Objectives: To determine if socio-demographic, medical and radiological variables have an impact on the risk of developing post-traumatic agitation in patients with mild complex to severe Traumatic Brain Injury (TBI). In addition, determine prognosis using the Extended Glasgow Outcome Scale (GOS-E), length of stay (LOS) and orientation at discharge of agitated patients with TBI. Methods: A retrospective observational study of all 778 patients admitted to the Montreal General Hospital, a tertiary specialized trauma centre, following a TBI that occurred between 2013 and 2015. Data was collected from the national trauma registry and TBI program database. Independent variables collected were socio-demographic, clinical, and neurological information. Dependent variables were LOS in days, non-pharmacological treatment, GOS-E at discharge, and discharge destination. Results: 55 patients (7.1%) suffered from post-traumatic agitation. The group with agitation had a significantly higher proportion of men, psychiatric history and suffered in a greater proportion a moderate TBI. The median GCS was significantly lower and post traumatic amnesia was longer in subjects with agitation. A higher percentage of patients with agitation were transferred to long-term care (LTC) facilities.